2007
DOI: 10.1007/s11605-006-0075-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Surgical Management of Gallbladder Cancer: A Review

Abstract: Gallbladder cancer is one of the most lethal carcinomas and continues to pose many challenges for surgeons. Identifiable risk factors for carcinoma of the gallbladder include cholelithiasis, an anomalous pancreaticobiliary junction, and focal mucosal microcalcifications. Adenocarcinoma is the primary histologic type in most patients and the tumor is frequently associated with Kras and p53 mutations. Radiologic and endoscopic advances in endoscopic ultrasonography and magnetic resonance cholangiopancreatogram, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
157
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(167 citation statements)
references
References 69 publications
2
157
0
8
Order By: Relevance
“…However, there is still no established standard regimen of adjuvant chemotherapy for GB cancer [16][17][18][19]. Traditionally, 5-fluorouracil-based chemotherapy regimen has been used as an adjuvant therapy for biliary tract malignancies including GB cancer [6,9,20,21]. Recently, gemcitabine-, capecitabine, or S-1-based regimens have been tried, and several studies have demonstrated somewhat promising results from GB cancer [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still no established standard regimen of adjuvant chemotherapy for GB cancer [16][17][18][19]. Traditionally, 5-fluorouracil-based chemotherapy regimen has been used as an adjuvant therapy for biliary tract malignancies including GB cancer [6,9,20,21]. Recently, gemcitabine-, capecitabine, or S-1-based regimens have been tried, and several studies have demonstrated somewhat promising results from GB cancer [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The 5 year mortality rate is up to 90% (2), while the median survival prognosis for patients is 4-6 months. Due to the advanced stage at presentation, only a third of patients are potential candidates for surgery (3). GBC is highly invasive and spreads to regional lymph nodes at an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation of GBCA remains unspecific and may include abdominal pain, weight loss, fever, and jaundice (9).…”
Section: Resultsmentioning
confidence: 99%